PEMBUATAN BODIESEL DARI CRUDE PALM OIL MENGGUNAKAN KATALIS CaO/KOH CANGKANG TELUR BEBEK - Tulistiowati; Noorma Kurnyawaty; Harjanto (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
Biodiesel is an alternative fuel source that can be produced from vegetable oil through a transesterification process. CPO (Crude Palm Oil) is one source of vegetable oil that has the potential to be used as a base material for biodiesel production. An important aspect of biodiesel production is the use of catalysts. Duck eggshell can be used as a heterogeneous base catalyst because it contains calcium carbonate (CaCO3) which can produce CaO through the calcination process. CaO catalyst was made by calcining duck eggshell at 800°C for 4 hours, then impregnated with 30% KOH solution. This research aims to make biodiesel from CPO oil using CaO/KOH catalyst from duck eggshell based on variation of oil:methanol mole ratio and catalyst mass. Then the esterification reaction of CPO aims to reduce the level of free fatty acids contained in the oil by using methanol and H2SO4 catalyst at 65°C. Free fatty acids decreased from 16.38% to 0.99%. Meanwhile, the transesterification reaction was carried out with variations of oil:methanol mole ratio (1:5, 1:7, 1:9, 1:11 and 1:13) and impregnated catalyst masses of 2% and 5%. The best biodiesel results were obtained in the variation of oil: methanol mole ratio 1:7 with 5% impregnated CaO catalyst and methyl ester content analyzed by GC-MS of 84.82%, yield of 43.24%, density of 0.89 g/mL, kinematic viscosity of 4.52 cSt and moisture content of 0.03%.